Update on transfusion-related acute lung injury: an overview of its pathogenesis and management - Yu, Yunhong; Lian, Zhengqiu (Frontiers in Immunology, 2023)
Transfusion-related acute lung injury (TRALI) is a severe adverse event and a leading cause of transfusion-associated death. Its poor associated prognosis is due, in large part, to the current dearth of effective therapeutic strategies. Hence, an urgent need exists for effective management and therapeutic strategies for the prevention and treatment of associated lung edema. Recently, various preclinical and clinical studies have advanced the current knowledge regarding TRALI pathogenesis. In fact, the application of this knowledge to patient management has successfully decreased TRALI-associated morbidity. This article reviews the most relevant data and recent progress related to TRALI pathogenesis. Based on the existing two-hit theory, a novel three-step pathogenesis model composed of a priming step, pulmonary reaction, and effector phase is postulated to explain the process of TRALI. TRALI pathogenesis stage-specific management strategies based on clinical studies and preclinical models are summarized with an explication of their models of prevention and experimental drugs. The primary aim of this review is to provide useful insights regarding the underlying pathogenesis of TRALI to inform the development of preventive or therapeutic alternatives.